Factors Factors Influencing the Effectiveness of Mathematics Teaching and Learning in High schools in Maryland County, Southeast Liberia. - Emmanuel Olagunju; Maria Fe Dumlao Gueta; Daniel Katu; 1Fallah Nyuamah; Gwendolyn Hedd -Williams (Universitas Muhammadiyah Kuningan, 2022)
Teaching and learning mathematics in junior and senior schools in Liberia has being a huge challenge which over time has resulted in limited progress in science, innovation, and economic advancement. However, in other to find practical solutions to this problem led to this research work wham's sole objective is to examine and elucidate the factors that influence Mathematics education in high schools and reveals how to effectively teach the subject in a developing country like Liberia. The research Investigation was done from the perspective of the school administrator, Mathematics teacher, and the students. The method adopted for data collection were open interview and semi-structured questionnaire, which was conducted and administered to a total of 11 administrators, 13 teachers and 160 students in the 8 educational districts in Maryland county. The findings of this work reveal that teachers are mostly responsible for ensuring that Mathematics education is effective